Adapting or maladapting: Building resilience to climate-related disasters in coastal cities. (February 2018) - Torabi, Elnaz; Dedekorkut-Howes, Aysin; Howes, Michael
Abstract: Despite the increasing risks associated with climate-related hazards, urban development in many coastal cities continues to take place on low-lying, high-risk land. Resilience is a key concept in adaptation, however, in the context of cities it is a complex phenomenon influenced by a diverse range of factors. This paper explores how the key elements of urban resilience (agents, institutions, and systems) interact to determine the types of approaches cities take to build resilience in two Australian cities. It uses case study data including semi-structured interviews with a diverse group of stakeholders ranging from local and state government authorities, non-government organisations, consulting firms, and researchers to the insurance industry. Findings indicate that the attitude of agents shapes the institutions and systems thus determining types of adaptation strategies in response to climate change. When the community's desire to live close to water couples with a lack of understanding or underestimation of the impacts, adaptation efforts are undermined. These findings call for a focus on the key role of agents for a transformational approach to building resilience that is based on shared learning. Highlights: Complexity of cities has made urban resilience a difficult concept to understand. The role of urban agents, institutions and systems in shaping resilience is explored. Agents play a bigger role in resilience by influencing institutions and systems. Community's perception of risk and a desire to live near water drive maladaptation. A transformational approach to resilience should focus on the role of agents.